2022
DOI: 10.3390/biom12020340
|View full text |Cite
|
Sign up to set email alerts
|

Are Cell-Based Therapies Safe and Effective in the Treatment of Neurodegenerative Diseases? A Systematic Review with Meta-Analysis

Abstract: Over the past two decades, significant advances have been made in the field of regenerative medicine. However, despite being of the utmost clinical urgency, there remains a paucity of therapeutic strategies for conditions with substantial neurodegeneration such as (progressive) multiple sclerosis (MS), spinal cord injury (SCI), Parkinson’s disease (PD) and Alzheimer’s disease (AD). Different cell types, such as mesenchymal stromal cells (MSC), neuronal stem cells (NSC), olfactory ensheathing cells (OEC), neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 129 publications
1
13
0
Order By: Relevance
“…α‐synuclein aggregates are known to be toxic to cells, leading to neuronal deaths in many α‐synucleinopathies (Hirschi et al., 2003 ). Neuronal cells release α‐synuclein aggregates by the process of exocytosis (Hirschi et al., 2003 ), which are then taken up via endocytosis by neurons and glial cells (Van den Bos et al., 2022 , Salem et al., 2014 , Mo et al., 2012 ). Furthermore, it is suggested that the interaction between α‐synuclein and N‐methyl‐D‐aspartate (NMDA) receptors could facilitate clathrin‐mediated endocytosis of NMDA receptors (Gomperts, 2016 ).…”
Section: Therapeutic Application Of Stem Cellsmentioning
confidence: 99%
“…α‐synuclein aggregates are known to be toxic to cells, leading to neuronal deaths in many α‐synucleinopathies (Hirschi et al., 2003 ). Neuronal cells release α‐synuclein aggregates by the process of exocytosis (Hirschi et al., 2003 ), which are then taken up via endocytosis by neurons and glial cells (Van den Bos et al., 2022 , Salem et al., 2014 , Mo et al., 2012 ). Furthermore, it is suggested that the interaction between α‐synuclein and N‐methyl‐D‐aspartate (NMDA) receptors could facilitate clathrin‐mediated endocytosis of NMDA receptors (Gomperts, 2016 ).…”
Section: Therapeutic Application Of Stem Cellsmentioning
confidence: 99%
“…Even among studies for the same disease and using the same cell type, there is large variability between these parameters. all results should be interpreted with caution (Grekhnev et al, 2022;Van-den-Bos et al, 2022). In terms of cell type selection: Transplanted cells should meet criteria regarding safety, efficacy, stability, reproducibility, and scalability before transplantation into patients.…”
Section: Safety Prospectsmentioning
confidence: 99%
“…In conclusion, despite 15 years since the first pilot trial with MSC in MS published, 9 only a very limited number of small studies have been reported, 6 providing only some preliminary information about treatment efficacy. The unfortunate results from the MESEMS clinical trial should be carefully considered, given that it enrolled the greatest number of patients of any study conducted thus far, along with the rigorous standardization procedure applied to the study, the cell manufacturing, and the statistical design.…”
mentioning
confidence: 99%
“…On the 'NO' side, Drs. Uccelli and Freedman mostly focus on the results of MESEMS, the largest investigator-initiated, randomised, double-blind, placebo-compared phase II study of MSCs in MS. 6 MEsenchymal StEm cells for Multiple Sclerosis (MESEMS) concluded that a single IV dose of autologous MSCs has no effect on MS disease activity, de facto providing a final answer to whether MSCs Visit SAGE journals online journals.sagepub.com/ home/msj SAGE journals…”
mentioning
confidence: 99%
See 1 more Smart Citation